GLP-1 Analogue Liraglutide Enhances SP-A Expression in LPS-Induced Acute Lung Injury through the TTF-1 Signaling Pathway. (22nd May 2018) - Zhu, Tao; Li, Changyi; Zhang, Xue; Ye, Chunyan; Tang, Shuo; Zhang, Wei; Sun, Jiayang; Huang, Niwen; Wen, Fuqiang; Wang, Daoxin; Deng, Huojin; He, Jing; et al.
Abstract : The reduction of pulmonary surfactant (PS) is essential for decreased pulmonary compliance and edema in acute lung injury (ALI). Thyroid transcription factor-1 (TTF-1) plays a major role in the regulation of surfactant protein-A (SP-A), the most abundant protein component of PS. Simultaneously, the glucagon-like peptide-1 (GLP-1) analogue can enhance SP-A expression in the lung. However, the underlying mechanism is still unknown. The purpose of this study was to explore whether liraglutide, a GLP-1 analogue, upregulates SP-A expression through the TTF-1 signaling pathway in ALI. In vivo, a murine model of ALI was induced by lipopolysaccharide (LPS). Pulmonary inflammation, edema, insulin level, ultrastructural changes in type II alveolar epithelial (ATII) cells, and SP-A and TTF-1 expression were analyzed. In vitro, rat ATII cells were obtained. SP-A and TTF-1 expression in cells was measured. ShRNA-TTF-1 transfection was performed to knock down TTF-1 expression. Our data showed that LPS-induced lung injury and increase in insulin level, and LPS-induced reduction of SP-A and TTF-1 expression in both the lung and cells, were significantly compromised by liraglutide. Furthermore, we also found that these effects of liraglutide were markedly blunted by shRNA-TTF-1. Taken together, our findings suggest that liraglutide enhances SP-A expression in ATII cells and attenuates pulmonary inflammation in LPS-induced ALI, most likely through the TTF-1 signaling pathway.